2017
DOI: 10.2106/jbjs.16.00734
|View full text |Cite
|
Sign up to set email alerts
|

Increased Mortality in Elderly Patients with Sarcopenia and Acetabular Fractures

Abstract: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 32 publications
3
57
0
1
Order By: Relevance
“…However, our results differed in the positive relationship between sarcopenia and 1‐year mortality. Our results are consistent with numerous previous publications demonstrating an association with mortality following major surgery for carcinoma, solid organ transplant, and orthopedic trauma 8,10 . These results support the concept that patients presenting with sarcopenia, whether due to disease burden or frailty, have decreased physiologic reserves and are predisposed to postsurgical complication and mortality.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, our results differed in the positive relationship between sarcopenia and 1‐year mortality. Our results are consistent with numerous previous publications demonstrating an association with mortality following major surgery for carcinoma, solid organ transplant, and orthopedic trauma 8,10 . These results support the concept that patients presenting with sarcopenia, whether due to disease burden or frailty, have decreased physiologic reserves and are predisposed to postsurgical complication and mortality.…”
Section: Discussionsupporting
confidence: 92%
“…Research assessing the prognostic value of malnutrition and sarcopenia in patients undergoing orthopedic surgery, as well as clinical interventions to mitigate this risk is largely limited to elderly patients with hip fractures 4,5 . Retrospective studies have demonstrated an association between sarcopenia and increased risk of complications and mortality following emergency abdominal surgery, trauma, carcinoma resection, solid organ transplant, elective aortic aneurysm repair, hip fractures, and acetabular fracture in elderly patients 6‐19 . We sought to study the prognostic impact of skeletal muscle mass, for example, sarcopenia, as well as patient‐, tumor‐, and treatment‐related factors on postoperative outcomes following excision and limb reconstruction for sarcoma of the extremities.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, an extrinsically defined sarcopenia threshold faces scrutiny as to the similarity between the study population and the populations for which those thresholds have been established. Both Deren et al 25 and Kaplan et al 18 used sarcopenia cut-off values from a 2008 study by Prado et al , which examined sarcopenic obesity in patients with solid tumors of the respiratory and gastrointestinal tract 8 26 27…”
Section: Discussionmentioning
confidence: 99%
“…7 In noncancer patients, CT-measured sarcopenia was associated with increased mortality in patients with chronic liver disease, chronic renal disease, pneumonia, and sepsis as well as in intensive care unit (ICU), trauma, vascular surgery, general surgery, orthopaedic surgery, and transplant patients. [44][45][46][47][48][49][50][51][52][53][54][55][56] In a cohort of 450 trauma patients age ! 65 years admitted to the ICU, CT-measured sarcopenia was associated with 1-year mortality.…”
Section: Consequences Of Sarcopeniamentioning
confidence: 99%